2010
DOI: 10.1111/j.1423-0410.2010.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐D Rh antibodies appearing after apheresis platelet transfusion: stimulation by red cells or microparticles?

Abstract: Despite RBC contamination of APs below commonly accepted thresholds for Rh immunogenicity, AP transfusion can provoke non-D Rh antibody formation. RBC-derived microparticles, smaller but more numerous than RBCs, are volumetrically comparable and may be a hitherto underappreciated antibody stimulus. Further microparticle research will guide considerations of extended phenotypic matching of platelet components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
(16 reference statements)
2
29
0
Order By: Relevance
“…These results are concordant with recent data published by Kitazawa et al [70] who stained RBCs and PLTs in the PLT samples with anti-glycophorin A and anti-CD41 to count residual RBCs and residual RBC derived microparticles. Microparticles are cell derived membrane vesicles that range in size between 0.1 and 1 µm [71] and express D antigen on their surface, if they are obtained from a D+ donor [72].…”
Section: Part 2: Plt Transfusion and The D Antigensupporting
confidence: 83%
See 3 more Smart Citations
“…These results are concordant with recent data published by Kitazawa et al [70] who stained RBCs and PLTs in the PLT samples with anti-glycophorin A and anti-CD41 to count residual RBCs and residual RBC derived microparticles. Microparticles are cell derived membrane vesicles that range in size between 0.1 and 1 µm [71] and express D antigen on their surface, if they are obtained from a D+ donor [72].…”
Section: Part 2: Plt Transfusion and The D Antigensupporting
confidence: 83%
“…However, as stated before, recent data from Kitazawa et al [70] showed that PLTs collected by apheresis contained a residual RBC volume and RBC-derived microparticle volume in the range of 0.4-0.8 µl and 0.1-1 µl, respectively. On a per-volume basis, these potential antigenic stimuli matched to within an order of magnitude, but the authors hypothesized that the smaller, more numerous RBC derived microparticles may be more immunogenic than RBCs themselves, because they could easily be phagocytosed by recipient antigen presenting cells.…”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast to this study, Villalba et al [9] and Reckhaus et al [10] presented data from RhD-different platelet (PLT) transfusions. Villalba et al retrospectively studied the formation of anti-D in a group of 48 RhD-female leukemia patients below 55 years of age (roughly 'childbearing age' and Heuft/Mansouri Taleghani Transfus Med Hemother 2018;45:148-150 150 [20] hypothesized that RBC microparticles could contribute to RBC alloimmunization. Microparticles can be phagocytosed and therefore could be as immunogenic as RBC.…”
mentioning
confidence: 99%